2017
DOI: 10.1371/journal.pone.0174402
|View full text |Cite
|
Sign up to set email alerts
|

"The evil virus cell": Students‘ knowledge and beliefs about viruses

Abstract: Education about virus biology at school is of pivotal interest to raise public awareness concerning means of disease transmission and, thus, methods to prevent infection, and to reduce unnecessary antibiotic treatment due to patient pressure on physicians in case of viral diseases such as influenza. This study aimed at making visible the knowledge of Austrian high school and university students with respect to virus biology, virus structure and health-education issues. The data presented here stem from compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 23 publications
1
22
0
3
Order By: Relevance
“…Obviously, a large fraction of the population has severe gaps when it comes to virus-related knowledge. This assumption finds corroboration in a study by Simon et al (2017) comparing such knowledge between secondary students in grades 7 and 10 and university students in their first year, studying either biology or nonscientific subjects. Biology freshmen displayed the best knowledge in terms of viruses.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Obviously, a large fraction of the population has severe gaps when it comes to virus-related knowledge. This assumption finds corroboration in a study by Simon et al (2017) comparing such knowledge between secondary students in grades 7 and 10 and university students in their first year, studying either biology or nonscientific subjects. Biology freshmen displayed the best knowledge in terms of viruses.…”
Section: Introductionmentioning
confidence: 64%
“…Only a few referred to vaccination as an important means to prevent contraction of certain viral diseases. Perhaps unsurprisingly, >75% of the 646 students participating in this study declared that they would want to know more about viruses, and that they had not gained sufficient virusrelated knowledge at school (Simon et al, 2017). Thus, it seems necessary to raise awareness of this topic both in preservice biology teacher education and among biology teachers at school.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another carefully designed study that recently emerged from the S|E|H field investigated the knowledge of Austrian students about viruses and antibiotics (Simon, Enzinger, & Fink, 2017). The authors found that students' (even undergraduate biology students') conceptual knowledge about viruses was far from deep enough to dismantle Zeyer and Dillon Disciplinary and Interdisciplinary Science Education Research (2019) (Sadler & Zeidler, 2005, p. 115).…”
Section: Medicine Educationmentioning
confidence: 99%